2012
DOI: 10.1111/j.1558-5646.2011.01536.x
|View full text |Cite
|
Sign up to set email alerts
|

SELECTION ON FLORAL DESIGN INPOLEMONIUM BRANDEGEEI(POLEMONIACEAE): FEMALE AND MALE FITNESS UNDER HAWKMOTH POLLINATION

Abstract: Plant-pollinator interactions promote the evolution of floral traits that attract pollinators and facilitate efficient pollen transfer. The spatial separation of sex organs, herkogamy, is believed to limit sexual interference in hermaphrodite flowers. Reverse herkogamy (stigma recessed below anthers) and long, narrow corolla tubes are expected to promote efficiency in male function under hawkmoth pollination. We tested this prediction by measuring selection in six experimental arrays of Polemonium brandegeei, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 97 publications
(132 reference statements)
1
56
1
Order By: Relevance
“…Here we describe selection on floral traits by hummingbirds in experimental populations, hereafter “arrays.” We then compare these results to our previous study examining selection by hawkmoths on P. brandegeei floral design, where we documented selection for reverse herkogamy through female function, and selection for narrow corolla tubes and high nectar sugar concentration through male function (Kulbaba and Worley ). Measurement of hummingbird foraging behavior, pollen deposition, and removal, in addition to the number of seeds set and sired by each plant, allowed us to compare various indices of reproductive success.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…Here we describe selection on floral traits by hummingbirds in experimental populations, hereafter “arrays.” We then compare these results to our previous study examining selection by hawkmoths on P. brandegeei floral design, where we documented selection for reverse herkogamy through female function, and selection for narrow corolla tubes and high nectar sugar concentration through male function (Kulbaba and Worley ). Measurement of hummingbird foraging behavior, pollen deposition, and removal, in addition to the number of seeds set and sired by each plant, allowed us to compare various indices of reproductive success.…”
mentioning
confidence: 85%
“…To measure selection by hummingbirds on the floral traits of P. brandegeei , we used a similar approach to our previous study that measured selection by hawkmoths (Kulbaba and Worley ). We presented arrays of plants to the ruby‐throated hummingbird ( Archilochus colubris ), and measured pollen movement (pollen removal and deposition), and selection gradients on floral traits through female (seeds set) and male (seeds sired) fitness.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Floral traits that increase pollinator attraction should evolve under selection for increased male fitness more so than for selection for increased female fitness. However, selection can also act on pollinator attraction through female function if pollen is limiting [18][22]. In S. officinalis , staminate flowers have wider corollas than pistillate flowers (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical studies of selection on male and female fitness in plants with hermaphroditic flowers have shown that this assumption is not always correct. In particular, when seed set is pollen limited, selection acts on floral traits through female function as well [18][22]. If increased pollinator visitation increases both male and female fitness, selection may result in a common phenotype for both pistillate and staminate phase flowers.…”
Section: Introductionmentioning
confidence: 99%